Development of methods for assessing oxidative stress caused by atmospheric aerosols - Sameenoi, Yupaporn, author; Henry, Charles S., advisor; Rovis, Tomislav, committee member; Farmer, Delphine K., committee member; Van Orden, Alan K., committee member; Kipper, Matthew J., committee member (Colorado State University. Libraries, 2012)
Extensive epidemiological studies show strong associations between the exposure to atmospheric aerosol particulate matter (PM) in the size range of 0.1- 10 µm and health problems, including respiratory, atherosclerosis and cardiovascular diseases. However, the mechanisms of PM-induced toxicity are poorly understood. A leading hypothesis states that airborne PM induces harm by generating reactive oxygen species in and around human tissues, leading to oxidative stress. To improve understanding of this effect, methods including biological assays and chemical assays for assessing oxidative stress caused by atmospheric aerosols have been developed and are described in this dissertation. For biological assays, a cleavable tag immunoassay (CTI) was developed with an ultimate goal of measuring multiple oxidative stress biomarkers in a single run. As a proof-of-concept, the multianalyte analysis system CTI was performed in competitive, non-competitive, and mixed formats for detection of small molecules and protein biomarkers simultaneously. For chemical assays, a microfluidic electrochemical sensor and a microfluidic paper-based analytical device (µPAD) have been developed for assessing aerosol oxidative stress in an area-based exposure study and a personal exposure study, respectively. The microfluidic electrochemical sensor was used for assessing aerosol oxidative stress by measuring the oxidative activity. The sensor was coupled directly to a Particle-into-Liquid-Sampler (PILS) to create an on-line aerosol sampling/analysis system. The system offers analysis with 3 minute temporal resolution, making it the best available temporal resolution for aerosol oxidative activity. The sensor was also used to analyze the ability of aerosols to generate hydroxyl radicals as another parameter for assessing aerosol oxidative stress. The ultimate goal of this system is to create an on-line monitoring system using a similar approach for oxidative activity analysis. As a first step toward this goal, assay optimization and system characterization in an off-line format employing flow injection analysis and amperometric detection, were carried out and presented in this dissertation. A microfluidic paper-based analytical device (µPAD) was developed for measuring oxidative activity of aerosol collected by a personal sampler. The system allows analysis with minimal sample preparation and requires 100-fold less particulate matter mass than existing analysis methods.